Estimation of Genetic Diversity among Genotypes of Fodder Oat based on Principal Component Analysis - Kujur, Monica Jyoti; Mehta, A. K.; Bilaiya, S. K.; Patil, Prakarti (International Journal of Bio-resource and Stress Management, 2017)
The present investigation was planned to assess genetic diversity for fodder yield and yield contributing traits in fifty oat genotypes including two checks from different geographic regions and were evaluated in randomized block design with three replications at Seed Breeding Farm, Department of Plant Breeding and Genetics, College of Agriculture JNKVV Jabalpur during rabi, 2014. The traits were studied through principal component analysis (PCA). Out of eighteen, ten principal components (PC1 to PC10) exhibited more than 0.5 eigen values and showed about 89.52% total variability among the characters studied. PC1 accounts mostly for yield related traits like penultimate leaf area, panicle weight, axis branch number, spikelets panicle-1, florets panicle-1 and grain yield. The combined variation among these traits was 23.342%. PC2 was contributed by both physiological and yield related traits which are days to 50% flowering, days to flower initiation, number of leaves plant-1 dry matter yield and grain fodder yield. PC3 include trait i.e. plant height. PC4 includes trait axis length. PC5 include by physiological trait i.e. days to maturity. PC6 include yield trait 1000 seed weight. On the basis of PC score germplasm like HFO-25, IC372418, IC372413 and JHO-11 can be used for development of new oat varieties. These information would be very useful to select potentially breeding lines for future oat improvement program.